A new strongly paramagnetic cerium-containing microporous MOF for CO2 fixation under ambient conditions. Issue 40 (29th September 2017) - Das, Sabuj Kanti; Chatterjee, Sauvik; Bhunia, Subhajit; Mondal, Abhishake; Mitra, Partha; Kumari, Vandana; Pradhan, Anirban; Bhaumik, Asim
Abstract : A new microporous Ce2 NDC3 MOF has been synthesized solvothermally and it displayed strong paramagnetism and high catalytic efficiency in CO2 fixation under ambient conditions for the synthesis of cyclic carbonates. Abstract : Metal organic frameworks (MOFs) bearing multicarboxylate linkers are in great demand for designing robust heterogeneous catalysts. A new microporous Ce(iii )-based metal organic framework (Ce2 NDC3 ) has been synthesized under solvothermal conditions, which showed strong paramagnetism and a CO2 uptake capacity of 1.64 mmol g −1 (7.23 weight%) at 273 K. The Ce2 NDC3 showed high catalytic activity in CO2 fixation for the synthesis of cyclic carbonates with a maximum yield of 92% at ambient temperature and pressure. This rare earth metal-based MOF has been well characterized by single crystal X-ray diffraction, PXRD, N2 adsorption/desorption, UHR-TEM, FESEM, FTIR, 13 C MAS NMR and TGA. Here, we have carried out magnetic analysis, which revealed that the Ce(iii ) in this MOF exhibited 2 F5/2 magnetism in the ground state. The Ce2 NDC3 catalyst showed high recycling efficiency in CO2 fixation reactions, together with retention of the MOF structure after several rounds of reuse. Presumably, the presence of acidic Ce(iii ) metal ions and microporosity in the coordinated polymer network is responsible for the high catalytic activity.